S100P promotes trophoblast syncytialization during early placenta development by regulating YAP1 - Zhou, Hanjing; Pan, Yibin; Yang, Weijie; Zhao, Chenqiong; Sun, Xiaohe; Hong, Binbin; Jin, Xiaoying; Zhang, Tai; Zhang, Yinli; Liu, Na; Zhang, Songying; Zhu, Haiyan (Frontiers in Endocrinology, 2022)
Recurrent pregnancy loss (RPL) is a severe complication of pregnancy that is caused by genetic abnormalities, immune dysfunction, aberrant cell biology, and tissue structure destruction. Among which, placental dysfunction is crucial in the pathogenetic progression of RPL. Although some regulatory factors associated with RPL have been elucidated, the placental changes correlated with RPL still need to be elucidated. Here, we found that a portion of RPL patients presented with low serum and placental S100P expression. Using a human trophoblast stem cell model, we demonstrated that S100P was exclusively expressed in syncytiotrophoblast (ST)-like syncytia (ST(2D)-TSCT) and that loss of S100P expression in ST(2D)-TSCT cells impaired β-hCG secretion, leading to syncytialization failure during early placental development. Moreover, we found that S100P is involved in regulating trophoblast syncytialization by downregulating the protein level of Yes-associated protein 1 (YAP1), which plays a pivotal role in maintaining trophoblast stemness. Together, our findings suggest that S100P plays an essential role in regulating trophoblast syncytialization during early placental development in humans via YAP1. Additionally, lower serum S100P levels may predict poor pregnancy outcomes and represent a potentially useful marker for evaluating placental biological function during early pregnancy.